2015
DOI: 10.1111/1365-2656.12455
|View full text |Cite
|
Sign up to set email alerts
|

How to capture fish in a school? Effect of successive predator attacks on seabird feeding success

Abstract: Prey aggregations, such as fish schools, attract numerous predators. This typically leads to the formation of multispecific groups of predators. These aggregations can be seen both as a place of increased competition and as a place of possible facilitation between predators. Consequently, the functional role of such predator-prey aggregation is uncertain, and its effect on individual feeding success is virtually unknown. Using underwater film footage of different predators feeding on fish schools during the sa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
68
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 63 publications
(83 citation statements)
references
References 66 publications
2
68
0
Order By: Relevance
“…Their results suggest that both surface-feeding species and diving species should have greater success when foraging together. Furthermore, a higher frequency of attacks, particularly if varied in direction in three-dimensional space, would prevent schooling prey from organizing themselves, and result in higher success rate among all predators (Lett et al, 2014;Thiebault et al, 2016).…”
Section: Positive Interactions Among Marine Predatorsmentioning
confidence: 99%
See 3 more Smart Citations
“…Their results suggest that both surface-feeding species and diving species should have greater success when foraging together. Furthermore, a higher frequency of attacks, particularly if varied in direction in three-dimensional space, would prevent schooling prey from organizing themselves, and result in higher success rate among all predators (Lett et al, 2014;Thiebault et al, 2016).…”
Section: Positive Interactions Among Marine Predatorsmentioning
confidence: 99%
“…; Hunt et al, 1988;Harrison et al, 1991;Veit et al, 1993), prey capture probably increases over some range of flock sizes. If this is true, then certainly population growth rates of seabirds that depend on finding feeding flocks to find sufficient food need to be linked to the presence, frequency and size of those flocks (Thiebault et al, 2016). Irons (1998) found that breeding black-legged kittiwakes returned to the same feeding areas, and selectively joined flocks in preferred feeding areas-with preference shown for large flocks, which were typically associations with diving auks (Uria).…”
Section: Future Researchmentioning
confidence: 99%
See 2 more Smart Citations
“…attack single peripheral prey individuals, and density attacks) are not uncommon (e.g. multi-species feedings)464748. Exposure to such conflicting, antagonistic predation pressures might have played a pivotal role in the evolution of collective behaviour.…”
mentioning
confidence: 99%